The Design Model of Multilevel Estimation Means for Students’ Competence Assessment at Technical Higher School - O. F. Shikhova (Образование и наука)
The paper considers the research findings aimed at the developing the new quality testing technique for students assessment at Technical Higher School. The model of multilevel estimation means is provided for diagnosing the level of general cultural and professional competences of students doing a bachelor degree in technological fields. The model implies the integrative character of specialists training - the combination of both the psycho-pedagogic (invariable) and engineering (variable) components, as well as the qualimetric approach substantiating the system of students competence estimation and providing the most adequate assessment means. The principles of designing the multilevel estimation means are defined along with the methodology approaches to their implementation. For the reasonable selection of estimation means, the system of quality criteria is proposed by the authors, being based on the group expert assessment. The research findings can be used for designing the competence-oriented estimation means.